Patients, Knowledge, Nursing Pro description of NURS PROFESSIONAL STUDENTS' KNOWLEDGE ABOUT INDEPENDENT NURSING INTERVENTIONS IN PATIENTS INTENSIVE CARE UNIT DR. T.C. HILLER MAUMERE: GAMBARAN PENGETAHUAN MAHASISWA PROFESI NERS TENTANG INTERVENSI MANDIRI KEPERAWATAN PADA PASIEN INTENSIVE CARE UNIT RSUD dr. T.C. HILLLERS MAUMERE - Guru, Yustina Yantiana (PENA NURSING, 2025)
Background: Independent nursing interventions are actions carried out by nurses without direct instructions from medical personnel, which aim to improve the quality of nursing care, especially for patients treated in the Intensive Care Unit (ICU). Nursing students as prospective professional nurses are expected to have adequate knowledge regarding independent interventions in clinical practice Objective. This study aims to determine the overview of nursing students' knowledge about independent nursing interventions in ICU patients at dr. T.C. Hillers Maumere Regional General Hospital. This type of research is descriptive with a quantitative approach. The research sample was taken by total sampling from all nursing students who are currently undergoing practice in the ICU. Data were collected using a closed questionnaire and analyzed descriptively. The results: Level of knowledge of nursing professional students regarding independent nursing interventions in the ICU Results and Discussion: he results showed that the majority of respondents had a good level of knowledge (98%) regarding independent nursing interventions, including interventions for pain management, prevention of pressure ulcers, meeting nutritional needs, and psychological support. Conclusion: These results are expected to be used as material for evaluating and strengthening the nursing professional education curriculum to emphasize the mastery of independent interventions appropriate to the critical condition of patients in the ICU.